2016
DOI: 10.1007/s10482-016-0749-7
|View full text |Cite
|
Sign up to set email alerts
|

Paraburkholderia caffeinitolerans sp. nov., a caffeine degrading species isolated from a tea plantation soil sample

Abstract: A Gram-stain negative, facultatively anaerobic, non-sporulating, non-motile and rod-shaped bacterium, designated CF3, was isolated from a tea plantation soil sample and its taxonomic position was determined using polyphasic taxonomy. Strain CF3 displayed optimum growth at 25 °C, pH 5.0 and in the presence of 0-1 % NaCl. Comparative phylogenetic analysis of the 16S rRNA, recA and gyrB gene sequences showed that the isolate belongs to the genus Paraburkholderia, showing high levels of similarity with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Species were considered heterotypic synonyms if the genomes of both type strains possessed ANI values > 97%. Synonyms included “ Paraburkholderia caffeinitolerans ” ( Gao et al, 2016 ) and “Paraburkholderia dokdonella ” ( Jung et al, 2019 ); with a 99.9% pairwise ANI value, and were subsequently merged into the earlier synonym “ P. caffeinitolerans ” ( Figure 2 ). Paraburkholderia insulsa ( Dobritsa and Samadpour, 2016 ) type strain possessed an ANI value of 98.4% compared to Paraburkholderia fungorum ( Coenye et al, 2001a ; Sawana et al, 2014 ), and was subsequently merged into the earlier synonym P. fungorum ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Species were considered heterotypic synonyms if the genomes of both type strains possessed ANI values > 97%. Synonyms included “ Paraburkholderia caffeinitolerans ” ( Gao et al, 2016 ) and “Paraburkholderia dokdonella ” ( Jung et al, 2019 ); with a 99.9% pairwise ANI value, and were subsequently merged into the earlier synonym “ P. caffeinitolerans ” ( Figure 2 ). Paraburkholderia insulsa ( Dobritsa and Samadpour, 2016 ) type strain possessed an ANI value of 98.4% compared to Paraburkholderia fungorum ( Coenye et al, 2001a ; Sawana et al, 2014 ), and was subsequently merged into the earlier synonym P. fungorum ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our phylogenomic and ANI analyses ( Figures 1 and S2 ) indicated that, at least from a genomic standpoint, the species “ P. atlantica ”, “ P. bonniea ”, “ P. caffeinitolerans ”, and “ P. hayleyella ” represent new species ( Gao et al, 2016 ; Brock et al, 2020 ; Paulitsch et al, 2020a ). Despite displaying near-cutoff ANI values, not only Paraburkholderia dioscoreae and Paraburkholderia xenovorans but also Paraburkholderia youngii and “P.…”
Section: Resultsmentioning
confidence: 94%
“…“ Paraburkholderia caffeinitolerans ” was isolated from a Chinese tea plantation soil and showed caffeine degrading abilities ( Gao et al, 2016 ). Years later, a Korean strain isolated from the rhizosphere of Campanula takesimana was described as the new species “ Paraburkholderia dokdonella ” ( Jung et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation